OPTIMIZATION OF MICROCLIMATE IN LIVESTOCK BUILDINGS AS A KEY FACTOR IN PREVENTING DISEASES IN CALVES - Колечко, Аліна; Пікула, Оксана (Modern engineering and innovative technologies, 2025)
The article analyzes the impact of microclimatic conditions in calf housing on their health, with a particular focus on the prevention diseases. Key microclimate parameters (temperature, relative humidity, air velocity, concentration of harmful gases, du